Effect on exam performance through massive open online courses versus face-to-face classrooms among Indian medical students: An analytic study - Janpreet Singh Kala; Avi tyag; B Subhash; V D S Jamwal; Aseem Tandon (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: With the affluence of use and better accessibility, Massive Open Online Courses (MOOCs) have become essential in imparting education in the ongoing COVID scenario. The study aims to compare the effect of MOOCs versus face-to-face classrooms on medical students' learning outcomes in anatomy exams at the end of the first year of a medical course. Materials & Methods: The cross-sectional study included 300 first-year Bachelor of Medicine and Bachelor of Surgery (MBBS) students in two batches (150 each). The first group underwent a one-year MOOCs group, and the second group experienced a one-year face-to-face classroom. The training program and study materials for the anatomy curriculum were kept the same for both groups by the standard National Medical Council curriculum of India. The assessment was standardized and based on summative University examinations. Results: The mean score in the university theoretical exam was significantly higher in the MOOCs group as compared to the classroom learning group (66.68 ± 6.61 vs 63.52 ± 7.97, P-value: 0.001), whereas the mean scores in the practical examination were significantly higher in classroom learning group as compared to MOOCs group (78.71 ± 6.28 vs. 74.19 ± 7.45, P-value: 0.001). The MOOCs group shows better learning in the cognitive domain. Conclusion: The classroom learning groups performed better in the practical examination, which assesses the psychomotor and affective domain of learning. Hence, a blended T/L method involving both classroom and online methods is recommended as India's preferred approach to imparting medical education.